Antibacterial activity test of liquid soap with the addition of ylang ylang flower essential oil (cananga odorata) against the growth of escherichia coli and staphylococcus aureus bacteria - Lestari, Eni; Rasyidah, Rasyidah (Science Midwifery, 2024)
Liquid soap with the addition of Ylang ylang flower (Cananga odorata) flower essential oil offers the potential to be an effective antibacterial product. This research aims to evaluate the quality of liquid soap formulated with Ylang ylang flower essential oil and conduct trials on its effectiveness regarding Escherichia coli and Staphylococcus aureus. This research applies quantitative experimental methods, which were chosen because the research was carried out in a laboratory setting with an experimental approach. This method aims to assess the suitability of the products tested by researchers. Next, the results of observations regarding the inhibition zone will be analyzed using a table to evaluate the effectiveness of the product. The research results showed that all liquid soap formulations met SNI standards in terms of organoleptics, pH, homogeneity, viscosity and foam height. The activity of Ylang ylang flower essential oil concentrations of 5% and 10% has antibacterial activity in the medium category, while at a concentration of 15% it shows strong antibacterial activity with the highest inhibition zone diameter, namely 11.9 mm against Escherichia coli and 12.7 mm against Staphylococcus aureus. Thus, liquid soap containing Ylang ylang flower essential oil has been proven to be effective in increasing antibacterial activity, especially at a concentration of 15%, and meets all quality standards in accordance with SNI.